DETEKSI FLUKTUASI CADANGAN DEVISA DI TIGA NEGARA BERKEMBANG (PENDEKATAN MODEL ANALISIS PANEL ARDL DAN TSLS) - Maya Syaula (CV. HAWARI, 2021)
This study aims to analyze the detection of fluctuations in foreign exchange reserves in three developing countries. This study uses secondary data or time series. The data equation model in this study is the Simultaneous Regression Analysis model and the ARDL Panel. Simultaneous analysis results in equation 1 show that based on the results of simultaneous equation research data analysis, it is known that foreign exchange reserves are significantly affected by inflation, economic growth and foreign debt. The results of the simultaneous influence analysis in equation 2 show that based on research data, the variables of exports, inflation and foreign exchange reserves have an effect on foreign debt. The results of the ARDL panel analysis show that foreign exchange reserves are the leading indicator in three developing countries (Indonesia, Vietnam and Malaysia) but their position is unstable in the short run.